High genetic variability of Alexandrium catenella directly detected in environmental samples from the Southern Austral Ecosystem of Chile. (February 2018) - Cruzat, Fernando A.; Muñoz, Christian; González-Saldía, Rodrigo R.; Inostroza, Agar; Andree, Karl B.
Abstract: Chilean waters are often affected by Alexandrium catenella, one of the leading organisms behind Harmful Algae Blooms (HABs). Genetic variability for this species are commonly carried out from cultured samples, approach that may not accurately quantify genetic variability of this organism in the water column. In this study, genetic variability of A. catenella was determined by sequencing the rDNA region, in water samples from the Canal Puyuhuapi (South Austral Ecosystem of Chile). A. catenella was detected in 8, 8% of samples analysed. All sequences obtained were A. catenella (Tamara complex group I), with three highly frequent haplotypes (34%), and twenty new haplotypes. These haplotypes increase the genetic variability from 2.8% to 3.14% in this area. Through this new method, genetic determination of A. catenella can accurately be monitored and ecological studies of this species can be implemented. Highlights: Molecular detections of A. catenella were made directly from water samples. High genetic diversity was determinate compared to cultured samples. rDNA analysis increase 154% haplotypes described of A. catenella. rDNA analysis allow to study the genetic diversity of A. catenella at worldwide scale.